Expiratory airflow in late adolescence and early adulthood in individuals born very preterm or with very low birthweight compared with controls born at term or with normal birthweight: a meta-analysis of individual participant data. Issue 8 (August 2019) - Doyle, Lex W; Andersson, Sture; Bush, Andy; Cheong, Jeanie L Y; Clemm, Hege; Evensen, Kari Anne I; Gough, Aisling; Halvorsen, Thomas; Hovi, Petteri; Kajantie, Eero; Lee, Katherine J; McGarvey, Lorcan; et al.
Summary: Background: Maximal expiratory airflow peaks early in the third decade of life, then gradually declines with age. The pattern of airflow through adulthood for individuals born very preterm (at <32 weeks' gestation) or with very low birthweight (<1501 g) is unknown. We aimed to compare maximal expiratory airflow in these individuals during late adolescence and early adulthood with that of control individuals born with normal birthweight (>2499 g) or at term. Methods: We did a meta-analysis of individual participant data from cohort studies, mostly from the pre-surfactant era. Studies were identified through the Adults born Preterm International Collaboration and by searching PubMed and Embase (search date May 25, 2016). Studies were eligible if they reported on expiratory flow rates beyond 16 years of age in individuals born very preterm or with very low birthweight, as well as controls born at term or with normal birthweight. Studies with highly selected cohorts (eg, only participants with bronchopulmonary dysplasia) or in which few participants were born very preterm or with very low birthweight were excluded. De-identified individual participant data from each cohort were provided by the holders of the original data to a central site, where all the data were pooled into one data file. Any data inconsistencies were resolved by discussion with the individual sites concerned. Individual participant data on expiratory flow variables (FEV1, forced vital capacity [FVC], FEV1 /FVC ratio, and forced expiratory flow at 25–75% of FVC [FEF25–75% ]) were converted to Z scores and analysed with use of generalised linear mixed models in a one-step approach. Findings: Of the 381 studies identified, 11 studies, comprising a total of 935 participants born very preterm or with very low birthweight and 722 controls, were eligible and included in the analysis. Mean age at testing was 21 years (SD 3·4; range 16–33). Mean Z scores were close to zero (as expected) in the control group, but were reduced in the very preterm or very low birthweight group for FEV1 (−0·06 [SD 1·03] vs −0·81 [1·33], mean difference −0·78 [95% CI −0·96 to −0·61], p<0·0001), FVC (−0·15 [0·98] vs −0·38 [1·18], −0·25 [–0·40 to −0·10], p=0·0012), FEV1 /FVC ratio (0·14 [1·10] vs −0·64 [1·35], −0·74 [–0·85 to −0·64], p<0·0001), and FEF25–75% (−0·04 [1·10] vs −0·95 [1·47], −0·88 [–1·12 to −0·65], p<0·0001). Similar patterns were observed when we compared the proportions of individuals with values below the fifth percentile. Interpretation: Individuals born very preterm or with very low birthweight are at risk of not reaching their full airway growth potential in adolescence and early adulthood, suggesting an increased risk of chronic obstructive pulmonary disease in later adulthood. Funding: National Health and Medical Research Council (Australia), University of Bergen, Western Norway Regional Authority, National Institute for Health Research (UK), Stichting Astmabestrijding, St Olav's Hospital's Research Fund, Academy of Finland, European Commission, National Institute of Child Health and Human Development (USA), Victorian Government's Operational Infrastructure Support Program.